2000
DOI: 10.1161/01.cir.101.21.2454
|View full text |Cite
|
Sign up to set email alerts
|

Edge Restenosis After Implantation of High Activity 32 P Radioactive β-Emitting Stents

Abstract: We compared the results of lesions treated with single radioactive BX stents with an activity of 12 to 21 microCi (group 2, n = 54 lesions) with the results of lesions treated by single radioactive BX stents with an initial activity level of 3 to 12 microCi (group 1, n = 42 lesions). There were no procedural events. At the 6-month follow-up, no myocardial infarctions, deaths, or stent thromboses had occurred. Intrastent binary restenosis was 0% in group 1 versus 4% in group 2 (n = 2, both at the ostium of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 8 publications
2
81
0
9
Order By: Relevance
“…18 In patients treated with radioactive stents, edge stenosis has proved to be an important clinical problem, occurring in 30% of patients. 8,19 TAXUS II confirmed that no edge effect greater than that found with a BMS occurs with either MR or SR paclitaxel-eluting stents. As reported previously, the term "edge effect" is used to connote an effect greater than would be seen with BMS.…”
Section: Edge Effects and Restenosismentioning
confidence: 74%
See 2 more Smart Citations
“…18 In patients treated with radioactive stents, edge stenosis has proved to be an important clinical problem, occurring in 30% of patients. 8,19 TAXUS II confirmed that no edge effect greater than that found with a BMS occurs with either MR or SR paclitaxel-eluting stents. As reported previously, the term "edge effect" is used to connote an effect greater than would be seen with BMS.…”
Section: Edge Effects and Restenosismentioning
confidence: 74%
“…As reported previously, the term "edge effect" is used to connote an effect greater than would be seen with BMS. 8,19 In fact, there was a slight but nonsignificant decrease in edge stenosis compared with BMS. Edge stenosis (diameter stenosis Ͼ50%) rates for BMS were 3.4% (proximal) and 3.1% (distal), whereas for the SR and MR groups, the rates were 1.6% and 2.3% at the proximal and distal edges, respectively.…”
Section: Edge Effects and Restenosismentioning
confidence: 92%
See 1 more Smart Citation
“…1,2,3 Histological follow-up in the porcine model, however has indicated that late neointimal hyperplasia can recur at 90 and 180 days (Andrew J. Carter, DO, unpublished data, 2001). Thus, there are sufficient concerns about delayed healing with consequent risks of late restenosis 4 and thrombosis, 5 late malapposition, 6 edge effect, 7 and, on the other hand, delayed restenosis, 8 to warrant additional late follow-up catheterization. The objective of this study was to determine angiographic, intravascular ultrasound (IVUS), and clinical outcome up to 2 years after implantation of sirolimus-eluting stents in de novo coronary lesions.…”
mentioning
confidence: 99%
“…Animal studies have demonstrated several important similarities in histological characteristics between antiproliferative drug-eluting stents and intracoronary radiation therapy, which raises the concern of potential negative edge effects, 18 unhealed dissections, 19 or late stent-vessel wall malapposition. 20 In this study population, however, none of those morphological complications were detected at 6-month follow-up.…”
Section: Complications Assessed By Ivusmentioning
confidence: 99%